Retracted: Selection and Optimization of Regional Economic Industrial Structure Based on Fuzzy k-Means Clustering Algorithm - Intelligence and Neuroscience, Computational (Computational intelligence and neuroscience, 2023)
[This retracts the article DOI: 10.1155/2022/4278524.].